The importance of intercultural competence in foreign language teaching, with reference to tourism curricula in higher education - Tomić Mladen; Čolić Danijela (University Educons, Faculty of Sports and Tourism, Novi Sad, 2019)
Over the past several decades, tourism industry has seen constant growth on a global scale, not only in terms of the number of international tourists and the number of persons employed in tourism, but also in terms of its global GDP share. Such a growth entails the need for a greater number of qualified tourism experts, as well as for more advanced language competences, but also those intercultural and communicative competences that correspond to pertaining educational profiles and professional challenges. Most tourism curricula at European universities contain one or more foreign language courses. That language is most commonly English, while languages most commonly featured as second are German, Spanish and Italian. It is questionable whether, besides professional language competences which universities target as their primary outcome, those courses can adequately prepare future tourism professionals for work in their field or if they offer only general linguistic knowledge. The goal of this paper is to point to the necessity to include intercultural competences in foreign language teaching, so the future tourism professionals would master not only communication skills, but also those skills that would enable them a meaningful engagement in the contexts that require intercultural interaction.